Elastoplastic Stability and Failure Analysis of FGM Plate with Temperature Dependent Material Properties under Thermomechanical Loading - Sharma,Kanishk (2017)
Abstract The present paper explores the stability and failure response of elastoplastic Ni/Al2O3 functionally graded plate under thermomechanical load using non-linear finite element formulation based on first-order shear deformation theory and von-Karman’s nonlinear kinematics. The temperature dependent thermoelastic material properties of FGM plate are varied in the thickness direction by controlling the volume fraction of the constituent materials (i.e., ceramic and metal) with a power law, and Mori-Tanaka homogenization scheme is applied to evaluate the properties at a particular thickness coordinate of FGM plate. The elastoplastic behavior of FGM plate is assumed to follow J2-plasticity with isotropic hardening, wherein the ceramic phase is considered to be elastic whereas the metal is assumed to be elastic-plastic in accordance with the Tamura-Tomota-Ozawa model. Numerical studies are conducted to examine the effects of material and geometrical parameters, viz. material in-homogeneity, slenderness and aspect ratios on the elastoplastic bucking and postbuckling behavior and the failure response of FGM plate. It is revealed that material gradation affects the stability and failure behavior of FGM plate considerably. Furthermore, it is also concluded that FGM plate with elastic material properties exhibits only stable equilibrium path, whereas the elastoplastic FGM plate shows destabilizing response after the ultimate failure point.